Emergency Reporting Procedure in a Multi-National Environment - Salenka, Frantisek; Salenka, Dusana; Furi, Marian (Communications - Scientific letters of the University of Zilina, 2011)
This article is aimed on reporting procedure in emergency situation used in multi-national environment. It is based on real procedures, documents and instructions, which are usually used in all kinds of emergency assets, especially during the activities of multi-national joint forces. The first impulse for creating this procedure started in armed task forces and due to the great effect fluently increased to the civilian sector. The article is a basic instruction how to simply ensure information flowchart among all the elements and secure quick reaction on developing crisis situation.